Association of bowel movement frequency and laxative use with risk of hepatocellular carcinoma in US women and men. Issue 8 (4th June 2021) - Long, Lu; Liu, Xing; Jin, Lina; Simon, Tracey; Ma, Wenjie; Kim, Mi Na; Yang, Wanshui; Meyerhardt, Jeffrey A.; Chan, Andrew T.; Giovannucci, Edward; Zhang, Xuehong
Abstract: Abnormal bowel movements have been related to a variety of hepatocellular carcinoma (HCC) risk factors such as dyslipidemia, diabetes and altered metabolism of bile acids and gut microbiota. However, little is known about whether bowel movement frequency affects the risk of developing HCC. We followed 88 123 women in the Nurses' Health Study (NHS) and 28 824 men in the Health Professionals Follow‐up Study (HPFS) for up to 24 years. The Cox proportional hazards regression model was used to calculate multivariable hazard ratios (HRs) and confidence intervals (95%CI). We documented 101 incident HCC cases. Compared to those with daily bowel movements, participants with bowel movement more than once per day had a multivariable HR of 1.93 (95%CI: 1.18 to 3.16) in the pooled cohorts. For the same comparison, the positive association appeared stronger for men (2.72, 95% CI: 1.14 to 6.44) than for women (1.63, 95% CI: 0.87 to 3.06) but there was no statistically significant heterogeneity by sex ( P ‐value = .31). We found null associations between bowel movement every 2 days or less and the risk of HCC (HR = 1.05, 95%CI: 0.62 to 1.79). The HR (95%CI) for participants who used laxatives regularly relative to those who never used laxatives was 1.00 (0.64 to 1.55). Our results suggest participants with bowel movement more than once daily is associated with a higher risk of developing HCC compared to those with daily bowel movements. These findings need to be confirmed and potential mechanisms underlying this association need to be elucidated. Abstract : What's new? Bowel movement frequency has been suggested to play a role in cancer development. However, limited epidemiology studies have yielded mixed results, further complicated by the widespread use of laxative. Using data from two large prospective U.S. cohort studies, here the authors show for the first time that bowel movement more than once daily is associated with a higher risk of developing hepatocellular carcinoma. No association was observed between laxative use and hepatocellular carcinoma risk. The results suggest that intestinal functioning may influence hepatocellular carcinoma development, and future studies are warranted in more diverse racial/ethnic populations and to elucidate potential mechanisms.